2022
DOI: 10.2991/aebmr.k.211225.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Features and Market Segmentation of the Credit Card Industry in Malaysia

Abstract: To operate successfully in this credit card industry, various kinds of credit cards are offered to distinct user groups. This empirical study is conducted in Malaysia, and it examines the features of different types of credit card available. By using descriptive and one-way ANOVA test, this study analyses data of 234 credit cards which were collected from ringgitplus.com and imoney.my websites. The cards are categorised based on the usage purpose like airline tickets, insurance, dining, entertainment, fuel, li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Due to the lack of these issues, confidence and responsible behaviour of the students are not reflected in their attitude regarding credit card use. A study on employees of Malaysian institutions of higher learning found that college students generally hold positive attitudes towards credit card usage (Alam et al, 2022). A study revealed Bihar, India by Verma et al, (2019) where the loan for just one course is insufficient to support additional academic success.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of these issues, confidence and responsible behaviour of the students are not reflected in their attitude regarding credit card use. A study on employees of Malaysian institutions of higher learning found that college students generally hold positive attitudes towards credit card usage (Alam et al, 2022). A study revealed Bihar, India by Verma et al, (2019) where the loan for just one course is insufficient to support additional academic success.…”
Section: Introductionmentioning
confidence: 99%